Pengembangan Media Parita Untuk Meningkatkan Kemampuan Sosial Emosional Pada Masa Transisi PAUD Ke SD - Rani Rohmatu Masruroh; Ervin Nurul Affrida (Pendidikan Guru PAUD, FKIP, Univ Muhammadiyah Tasikmalaya, 2025)
Emotional social skills influence children's readiness to transition from early childhood education (PAUD) to elementary school, particularly in terms of difficulties in interaction and self-adjustment. The research developed a learning media product regarding emotional social skills, namely Parita, as a solution to assess children's readiness during the PAUD to SD transition. This research utilized the R&D development model based on Borg & Gall (1983), adapted into eight stages. The pre-test and post-test designs were used in this study while also applying both quantitative and qualitative data collection methods. Data collection methods were sourced from validation questionnaires for the material, validation for the Parita media, and assessment instruments when used by children. Based on a series of research stages, it was found that before the intervention, four subjects tended to have low emotional social skills. Parita, as an innovative learning media solution, is categorized as 'suitable' for assessing children's emotional social readiness. After being treated with Parita, an increase in social-emotional skills was found in four subjects. The social-emotional readiness during the transition from Early Childhood Education (PAUD) to elementary school for children aged 5-6 years at TKS Melati Surabaya also successfully improved, as evidenced by the post-test results.